VEGF-A in Serum and Plasma Rich in Growth Factors (PRGF) Eye Drops - Sanak, Frantisek; Baenninger, Philipp; Iselin, Katja; Kaufmann, Claude; Bachmann, Lucas; Buhl, Daniela; Thiel, Michael (Klinische Monatsblätter für Augenheilkunde, 2022)
Background Vascular endothelial growth factor (VEGF)-A, the most abundant subtype of the VEGF family in the eye, plays an important role in corneal homeostasis due to its ability to mediate corneal nerve repair. Repeated intravitreal anti-VEGF injections were shown to significantly reduce corneal nerve density, which might negatively affect corneal homeostasis and lead to a neuropathic dry eye disease. Currently, there are two effective modalities to treat dry eye while supplying VEGF to the ocular surface: serum eye drops (SED) and eye drops manufactured from plasma rich in growth factors (PRGF). The purpose of this study was to measure the VEGF-A concentration in SED and PRGF eye drops.Material and Methods Ten healthy volunteers donated blood on two separate occasions, 2 – 8 days apart. Thus, a total of 20 blood samples were processed to obtain both SED and PRGF. Concentrations of VEGF-A were quantified by a Simple Plex platform run in triplicate.Results The VEGF-A concentration in SED and PRGF was very similar between the two blood samples drawn from one individual donor but showed substantial interindividual variability. However, in all 20 samples, VEGF concentrations were substantially higher in SED samples (mean 238.7 ± 146.6 pg/mL) compared to PRGF samples (mean 67.4 ± 46.3 pg/mL). Based upon the analysis of variance (ANOVA) model for the measured concentrations with fixed effects for specimen (SED vs. PRGF) and subject, the mean difference between the SED and PRGF concentration was 168.1 pg/mL (95% confidence interval: [142.4, 193.9], p < 0.001).Conclusion Our study showed that the VEGF concentration was higher in SED than in PRGF. This is an important finding, particularly for potential treatment of dry eye disease in patients with neuropathic eye disease, especially in patients that received repeated anti-VEGF intravitreal injections, or in patients with Sjögrenʼs disease, where the level of VEGF in tears might be pathologically decreased. Hypothetically, VEGF might be needed to restore ocular surface homeostasis. Although growing evidence has shown that VEGF-A plays an important role in corneal homeostasis, only a randomized prospective clinical trial will show whether supplying VEGF-A to the ocular surface might successfully restore the corneal homeostasis and overcome the problem of corneal neuropathy in these patients. For such a trial, based on our results, an undiluted SED should be preferred over a PRGF due to the higher content of VEGF-A.
Keywords: cornea; conjunctiva; lids